2009
DOI: 10.1161/strokeaha.108.541177
|View full text |Cite
|
Sign up to set email alerts
|

Inducible Nitric Oxide Synthase Promoter Polymorphism Affords Protection Against Cognitive Dysfunction After Carotid Endarterectomy

Abstract: Background and Purpose-Cognitive dysfunction occurs in 9% to 23% of patients during the first month after carotid endarterectomy (CEA). A 4-basepair (AAAT) tandem repeat polymorphism (either 3 or 4 repeats) has been described in the promoter region of inducible nitric oxide synthase (iNOS), a gene with complex roles in ischemic injury and preconditioning against ischemic injury. We investigated whether the 4-repeat variant (iNOS ϩ ) affects the incidence of cognitive dysfunction after CEA. Methods-One-hundred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…Age was dichotomized at 75 years and treated as a categorical variable (> 75 or ≤ 75 years). 3,21,31,32 All other factors were also treated categorically, and the results are presented as percentages of patients who satisfy the criteria for that variable. For univariate analyses, Student t-test, Wilcoxon rank-sum test, Fisher exact test, Pearson chi-square test, and simple logistic regression were used where appropriate.…”
Section: Neuropsychometric Evaluation and Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Age was dichotomized at 75 years and treated as a categorical variable (> 75 or ≤ 75 years). 3,21,31,32 All other factors were also treated categorically, and the results are presented as percentages of patients who satisfy the criteria for that variable. For univariate analyses, Student t-test, Wilcoxon rank-sum test, Fisher exact test, Pearson chi-square test, and simple logistic regression were used where appropriate.…”
Section: Neuropsychometric Evaluation and Statistical Analysismentioning
confidence: 99%
“…8,9,11,12,21,27 The underlying pathophysiology of this early cognitive dysfunction (eCD) is not completely understood, but data from a number of studies suggest that ischemic injury is a contributing factor, 3,21,31,32 related to hypoperfusion during intraoperative CA cross-clamping and/or to dislodgment of atheroemboli during vessel dissection and plaque removal.…”
mentioning
confidence: 99%
“…Recent studies implicate a genetic basis for post-CEA cognitive dysfunction 5 6. The presence of at least one apolipoprotein E (APOE)-ε4 allele, which is associated with plasma lipoproteins and is involved in the metabolism and transport of CNS lipids, has been associated with increased risk of cognitive dysfunction 1 month after CEA 5.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of at least one apolipoprotein E (APOE)-ε4 allele, which is associated with plasma lipoproteins and is involved in the metabolism and transport of CNS lipids, has been associated with increased risk of cognitive dysfunction 1 month after CEA 5. A more recent study demonstrated that an inducible nitric oxide synthase (iNOS) promoter polymorphism afforded protection against moderate/severe cognitive dysfunction 1 month after CEA 6. Based on our current understanding of these genes, the APOE-ε4 polymorphism may be related to neuronal membrane repair and remodelling after injury, while the iNOS promoter polymorphism may be related to global cerebroprotective ‘baseline preconditioning.’…”
Section: Introductionmentioning
confidence: 99%
“…Whether or not aged, hypertensive, or diabetic animals should be included in future preconditioning experiments was also discussed. In addition, data showing that inducible nitrous oxide synthase promoter polymorphism affords protection against cognitive dysfunction after carotid endarterectomy was reported by Dr. Raqeeb Haque (Columbia University) [9], and the results suggest that cognitive dysfunction could be an endpoint to measure success in future potential preconditioning trials.…”
mentioning
confidence: 80%